Dark Adaptometry and Optical Coherence Tomography Angiography in Huntington Disease. - Shah, Aaditya; Fuller, Spencer; Criswell, Susan; Apte, Rajendra S. (Journal of Ophthalmic & Vision Research)
Purpose: Huntington's Disease (HD) is a fully penetrant neurodegenerative disease leading to cognitive and motor disturbances. The retina may serve as a structural and functional extension of the central nervous system to identify biomarkers of HD using noninvasive imaging technology such as optical coherence tomography angiography (OCTA) and dark adaptometry. Methods: This case--control study included 12 HD participants (24 eyes) recruited from the Huntington's Disease Society of America Center of Excellence at Washington University in St. Louis along with 16 control participants (31 eyes). Disease-positive participants underwent imaging testing of retinal capillary density and foveal avascular zone utilizing OCTA along with dark adaptometry testing. Data were collected from November 2020 to February 2022. Results: Individuals with HD had a lower mean age-adjusted superficial foveal capillary density and a higher mean deep foveal capillary density compared to control subjects. There was no significant difference in the mean foveal avascular zone or in dark adaptometry testing between the two groups. Conclusion: This study suggests that changes in retinal biomarkers may exist in patients with HD and that additional investigations using multimodal techniques are warranted.